Effect of vincristine on oral cavity carcinoma in rhesus monkey (macaca mulatta) (Journal of Laboratory Animal Science, 2022)
An adult male rhesus monkey (Macaca mulatta ) presented a malocclusion of teeth/ jaw with slight swelling in the upper  mandible in particular on right upper canine with diffused growth in the lower incisor and was showing progressive loss in  the weight of the animal. Histopathology of the biopsied tissue confirmed the lesion as Squamous Cell Carcinoma (SCC).  The animal was treated with Vincristine sulphate for three consecutive days two weeks apart. During and after treatment,  there was gradual reduction in the growth with some changes in hematological parameters and weight. Squamous cell  carcinoma is one of the most common oral neoplasia in many species including macaques. Treatment with Vincristine  sulphate has a good response to prolong the life of the animal.
Keywords: Macaque; Squamous cell carcinoma; Vincristine